The analysis of Barn Owl from the Cradle of Humankind (South Africa) sheds new light on the evolution of common Barn Owl (Tyto alba). - (:unkn) unknown (My University, 2023)
Barn Owl remains (Aves, Tytonidae, Tyto) are a quite common finding in the various localities ofthe Cradle of Humankind (Gauteng, South Africa) and they have been reported since the firstmentions of fossil birds from this area. More recently, fossils of Common Barn Owl (Tyto alba)are reported from the Rising Star Cave and several remains of a Barn Owl tentatively referred tothe Common Barn Owl (Tyto cf. alba) are described from the Plio/Pleistocene transition atKromdraai and from the Early Pleistocene at Cooper’s Cave. This latter taxon is known by morethan 100 remains representing all the long bones and phalanges and it’s very similar in shape,size, and proportions to the extant Tyto alba, but it’s slightly smaller and shows some subtlemorphological differences in the long bones. Even if the differences in size and morphologyprevent its attribution to the extant species, they are not strong enough to describe it as a taxonnew for the science and could more likely represents an early stage in the Tyto alba lineage.The recent study of the Barn Owl remains found in the Bolt’s Farm complex revealed that anew, clearly bigger, species of Barn Owl inhabited the Cradle of Humankind during thePliocene, more than a million years before the taxon found at Kromdraai and Copper’s, fromwhich it is clearly distinguishable. The relationships between this new taxon and the extinct Tytorichae from the Early Pliocene of Langebaanweg are still obscure, even if the new form seemsless stout and more similar in proportion to the extant Tyto alba.The presence of three species of Barn Owls in South Africa during the Pliocene, with theyounger extremely similar to the extant Common Barn Owl, seems to reinforce the hypothesis ofan African origin of Tyto alba, as this continent yielded the oldest records of this taxon fromMorocco, Tanzania and South Africa, all of them dated around 2 million years ago.
Keywords: African Research